Synchrotron-based spectroscopy and imaging reveal changes in the cell-wall composition of barley leaves in defence responses to Blumeria graminis f. sp. tritici. Issue 3 (3rd July 2019) - Lahlali, Rachid; Song, Tao; Chu, Mingguang; Karunakaran, Chithra; Yu, Fengqun; Wei, Yangdou; Peng, Gary
Abstract: Plant cell walls (CW) are composed mainly of cellulose–hemicellulose networks embedded in a pectin matrix. CW apposition, including papilla formation, is often associated with plant defence responses to infection by fungal pathogens. In this study, synchrotron-based Fourier transform infrared (sFTIR) spectroscopy and focal plane array (FPA) imaging were explored to characterize changes in CW chemical composition of barley leaf epidermis inoculated with the powdery mildew fungus of wheat that was unable to infect the barley cultivar 'CDC Silky' successfully. Spectroscopic results showed increased intensity of peaks representing asymmetric and symmetric stretching vibrations that correspond to fatty acid groups, phenolics/lignin, cellulose, hemicellulose, pectins and glucans. sFTIR spectral data separated the inoculated samples (with papillae formation) from non-inoculated controls, based on CW components including lignin/phenolics, polysaccharides and glucans. These results were further verified with FPA imaging. This is the first report on using sFTIR spectroscopy and FPA imaging to analyse in situ composition of plant cell wall components in relation to host defence responses. These findings, especially the changes in cellulose, hemicelluloses, pectins and glucans, lend support to a proposed structure of effective papillae, as well as to callose-cellulose networks associated with the defence response of barley against powdery mildew. Increases in phenolics likely help strengthen CW, in addition to direct effects on pathogens. The results also demonstrate that sFTIR and FPA analyses can be useful to study plant–pathogen interactions, especially in determining the role of cell wall apposition in response to fungal infection.